Relationship among Maternal Perception of Childbirth Experience, Spiritual Health and Maternal-Infant Relationship in the Postpartum Women: A Cross-Sectional Study - Zohreh Akhtarkia; Mahnaz Akbari Kamrani; Maliheh Farid; Hoorvash Faraji Dana (Wolters Kluwer Medknow Publications, 2023)
Background: Birth represents an influential moment in women's lives that can be a powerful or traumatic experience. Therefore, the aim of this study was to assess the relationship among maternal perception of childbirth experience, spiritual health, and maternal-infant relationship in the postpartum women. Materials and Methods: This descriptive-analytical study was conducted on 305 postpartum women referred to Health Centers in Karaj. The data were collected using the Perception of Birth Scale (POBS), maternal postnatal relationship scale, and spiritual health questionnaire. Results: In this study, the mean (standard deviation (SD) age of the participants was 27.50 (5.56) years. The Spearman's correlation test results showed that there was a significant positive relationship among the maternal perception of childbirth experience, the general maternal-infant relationship (r = 0.34, p < 0.001), quality of relationship (r = 0.17, p = 0.002), pleasure with interaction (r = 0.32, p < 0.001), and absence of hostility (r = 0.28, p < 0.001). In addition, a positive relationship was observed among spiritual health and general maternal-infant relationship (r = 0.21, p < 0.001), pleasure in interaction (r = 0.08, p = 0.164), absence of hostility (r = 0.15, p = 0.008), and the maternal perception of childbirth experience (r = 0.11, p = 0.039). Conclusions: It seems that to promote maternal-infant relationship, health care providers should not only try to promote physical intimacy between mother and infant but also create a positive emotional state for the mother during birth.